Pola Distribusi dan Dinamika Komunitas Burung Di Kawasan Cibinong Science Center - Widodo, Wahyu; Sulystiadi, Eko (JURNAL BIOLOGI INDONESIA, 2016)
"Cibinong Science Center LIPI or CSCâs LIPI as an artificial habitat to the bird species conservation, especiallywith their ecological parks. This research was to study the distribution patterns and dynamics of birdcommunities in the CSCâs LIPI areas during 2005 to 2009 and on 2014. Transect Lineâs method was used inthis study. The results were 39 species of birds to live in the eight sites observation on 0.27 km2 areas.However, there are no significant effects, especially relationships between Margalefâs index value to area,cotton area closest distance to the river and their habitat situation. According to âmultiple linear regressionâanalysis show that ?= 3.626-0.69 area -1.31 cotton area closest distance to the river + 0.94 habitat situation,with determinant coefficient value (R2) = 0.161. The densities of nine species were found high. Those specieswere Lonchura punctulata (D=49.37 individuals/ha), Zosterops palpebrosus (D=22.2 individuals/ha),Collocalia linchi (D=15.00 individuals/ha), Orthotomus sutorius (D=12.70 individuals/ha), Lonchura maja(D=12.48 individuals/ha), Passer montanus (D=12.19 individuals/ha), Pycnonotus aurigaster (D=7.37individuals/ha), Dicaeum trochileum (D=6.07 individuals/ha) and Streptopelia chinensis (D=5.85 individuals/ha). The diversity indices value (Hâ) 1.52 to 2.51 and the evenness indices value (E) 0.52 to 0.86. Thesimilarities indices value (SI) of birds in the CSCâs LIPI will be compare to another places, i.e. the IPBcampus at Darmaga, Bogor or Yogyakarta State Universityâs campus in Yogyakarta showed no different,relatively. The IS value were 58.82 to 61.54%. Birds in the CSC parks were high dominant to occure in thelower strata (27.78â43.18%) and upper strata (50.43-70.83%), while in the middle strata (1.39-9.15%) tend tobe slightly. Most activities were carried by birds , especially foraging and calls. Although, the birds in the CSCparks also breeding, take a rest etc . The CSCâs LIPI parks at Cibinong could be used as a reference to thebirdâs artificial habitat model to others areas. Thatâs an important if the areas are industries complex or theCenter office of some government buildings. But, the composition and structure of the vegetation will bedeveloped in there should be to produce some natural food resources and safety well for breeding of birds.Keywords: bird species, ecological parks, artificial habitat, distribution patterns, dynamics communities